HUBUNGAN ANTARA AKTIVITAS PEMBELAJARAN BERBASIS STEAM DENGAN KUALITAS KEMANDIRIAN ANAK USIA DINI DI KELOMPOK B RA AL-KAUTSAR KOTA BANDUNG - Diana Handayani; Diana Handayani; Tuti Hayati; Nano Nurdiansyah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The results of the preliminary study in Group B RA Al-Kautsar show that, there is a gap between the high STEAM-based learning activity and the quality of independence in some children. On the one hand, when carrying out STEAM-based learning activities children are motivated to learn independently, confidently. However, on the other hand there are some children who are still lacking in developing the quality of their independence. This situation can be seen when the child conveys the phrase "can't do it mom" or "how can mom" and even "I don't want to do it until it's finished mom". This study uses a quantitative approach and correlation method. Data collection techniques in this study through observation and documentation. The results of data analysis on the STEAM-Based Learning Activity variable (Variable X) obtained an average value of 74. This value is in the 70-79 interval with a good category. While the data analysis on the variable Quality of Early Childhood Independence (Variable Y) obtained an average value of 77. This value is in the 70-79 interval with a good category. The relationship between STEAM-Based Learning Activities and the Quality of Early Childhood Independence obtained the correlation coefficient through the Spearman Rank formula of 0.64. This correlation coefficient number is in the high category because it is in the interval 0.600-0.799. The results of the significance test obtained the price ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ‚Â¡ÃƒÂ¢Ã¢â‚¬Å¾Ã…Â½ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ¢â‚¬â€œÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ‚Â¡ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ‚Â¢ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ¢â‚¬ÂºÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ¢â‚¬Â = 3.32 > ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ‚Â¡ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ‚Â¡ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ…Â½ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ‚ÂÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ¢â‚¬â„¢ÃƒÂ°Ã‚ÂÃ¢â‚¬ËœÃ¢â€žÂ¢ = 2.12 at a significance level of 5% and db = 16 of 2.12. That is, Ha is accepted and Ho is rejected, in other words, there is a positive and significant relationship between STEAM-based learning activities and the quality of early childhood independence.